Influence of situation motor abilities on 50m freestyle results - Durovic, M.; Okicic, T.; Madic, D.; Beretic, I.; Pesic, I.; .Trivun, M. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
The aim of this study was to determine the influence of situation motor abilities on swimming results in the 50 m freestyle in elite male swimmers. The sample of participants comprised of 16 swimmers (Age = 20.88 y 3.8yrs., Fina points = 661.69 +/- 36,72, 50m freestyle long course = 24.0 +/- 0.43 s), participants of the Open Championship of Serbia "Serbia Open 2017". The selection of participants was made based on the quality of performance i.e. the best 16 swimmers who participated in the A and B finals in the 50 m freestyle. Both races were recorded and analyzed with specialized software Kinovea. The basic situation motor abilities were calculated, including: stroke length, stroke index, stroke rate and stroke effectiveness. Swimming results on 50m was taken from the official race report. Regression analysis was used to determine the influence of of situation motor abilities on swimming results. The average swimming results significantly correlated with variables: stroke length (r = 0.425, p = 0.05), stroke index, (r = 0.594, p = 0.01) and stroke effectiveness (r = 0.445, p = 0.04). Results of regression analysis have shown statistically significant influence (p= .000) of following variables: stroke length, stroke index and stroke effectiveness, with multiple correlation coefficient of .99 (R= .991), and multipl correlation squared of .98, explaining about 98% of variance (R2= 0.978), on swimming results on 50m. Based on the results, we can conclude that swimmers who have greater values of stroke length, stroke index and stroke effectiveness be able to swim faster on 50m freestyle.